Requirements Elicitation for Geo-information Solutions - Sluter, Claudia Robbi; van Elzakker, Corné P. J. M.; Ivánová, Ivana [UNESP] (Taylor & Francis, 2017)
Geo-information solutions can achieve a higher level of quality if they are developed in accordance with a user-centred design that requires definition of the user requirements in the first step of solution construction. We treat a geo-information solution as a system designed to support human-based activities in a specific context through which solutions to contextual problems can be achieved via geographic knowledge. Geographic knowledge is a result of geo-data exploration, analysis, interpretation and dissemination with a given geo-information system. Taking the characteristics of geo-information systems into account, existing methods and techniques of requirements engineering may be applied for the design and implementation of geo-information solutions. Based on these considerations, here we present a generic framework that can aid geo-information experts, geo-informaticians and cartographers in the design and construction of more efficient, effective and satisfactory solutions.
Keywords: geoinformation solution; requirements elicitation; requirements engineering; user requirements